2020
DOI: 10.2174/1874434602014010281
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-based Survey of Rickettsia spp. and Coxiella burnetii in Mosquitoes (Diptera: Culicidae) from Fars Province, Southern Iran, during 2017-18

Abstract: Objectives: Since there have not been any studies on the roles of the Iranian mosquitoes in the transmission of Rickettsia spp. and Coxiella burneti, the present study investigates the roles of mosquitoes in the transmission of the pathogens using the PCR techniques for the first time in Iran. Methods: The present study was conducted in Fars province during the activity seasons of mosquitoes in 2017-18. The primer des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, Rickettsia spp. was not detected among adult mosquitoes from Fars province in southern Iran in 2017 and 2018 and in the blood of camels in central and southeastern Iran in 2019 [16,18]. In contrast, Rickettsia spp.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, Rickettsia spp. was not detected among adult mosquitoes from Fars province in southern Iran in 2017 and 2018 and in the blood of camels in central and southeastern Iran in 2019 [16,18]. In contrast, Rickettsia spp.…”
Section: Discussionmentioning
confidence: 94%
“…Climatic conditions, specific vectors, and natural host restriction are the contributory factors for the endemicity of R. conorii in the Mediterranean region, including North Africa, southern Europe, and the Middle East. Limited data are available regarding rickettsial infections in Iran [8][9][10][11][12][13][14][15][16][17][18]. In a study conducted in 1995, a high proportion of positive human sera were identified by a rickettsial enzyme-linked immunosorbent assay (ELISA) (45%) kit in Iran.…”
Section: Introductionmentioning
confidence: 99%